Penerapan Metode Quality Function Deployment dalam Pengembangan Produk Minuman “Matcha Boy” - Abraham, Ivan; Maulana, Rifky; Sihombing, Samuel Kevin; Anshari, Aqbil; Rohman, Muhammad Daffa Fadhlur; Darmawan; Hasibuan, Gabriel Alfredo; Samuel, Dumangga; Wahyudi, Rizqi (Jurnal Ilmu Sosial dan Humaniora, 2025)
The application of the Quality Function Deployment (QFD) method serves as a strategic approach to ensure alignment between consumer needs and the technical characteristics of the “Matcha Boy” beverage product, playing a crucial role in translating the voice of the customer (VoC) into measurable decision-making within the product development process. By combining qualitative and quantitative approaches, data were collected through direct observation, open and closed questionnaires, and in-depth interviews with business practitioners. The analysis results indicate that the most influential attributes on purchasing decisions are the authentic and consistent matcha flavor, affordable pricing, and fast and friendly service, while menu variety and attractive packaging design serve as supporting factors to strengthen brand image and enhance consumer experience. The development of the House of Quality (HoQ) matrix revealed that aspects such as ingredient formulation, matcha powder quality, sugar measurement control, and the selection of milk types have strong correlations with customer satisfaction levels, emphasizing that improving the quality of raw materials and ensuring flavor consistency should be the top priorities in the product development strategy. Overall, the application of the QFD method at “Matcha Boy” has proven effective in providing a systematic, efficient, and market-oriented development direction and serves as a model that can be adopted by MSME actors to enhance the competitiveness of contemporary beverage products in line with modern consumption trends.